Pengaruh Daya Tarik Promosi, Kemudahan Penggunaan, dan Risiko Terhadap Minat Menggunakan E-Wallet pada Mahasiswa di Kota Batam - Dewi Apri Yanti; Argo Putra Prima (Komunitas Dosen Indonesia, 2024)
E-wallets offer many conveniences to users, despite the convenience and practicality of e-wallets, many people are reluctant to use them. Several factors contribute to the interest in using e-wallets, including promotional attractiveness, ease of use, and risk. This study aims to test passively and simultaneously. This type of research is quantitative with data collection techniques carried out by distributing questionnaires through google forms which are measured on a Likert scale. Testing in this study uses descriptive analysis, instrument test, classical assumption test, influence test and hypothesis testing. The population in this study were students majoring in accounting in Batam City and who had registered on the PDDIKTI website (Directorate General of Higher Education) with a total of 1631 students. The sample in this study used Probability Sampling technique and sample determination using Slovin technique which amounted to 100 respondents. The results of the study simultaneously show that promotional attractiveness, ease of use and risk affect the interest in using e-wallets for students in Batam City. However, based on the results of this study partially show that Promotional Attractiveness affects the interest in using e-wallets for students in Batam City. Ease of Use affects the interest in using e-wallets for students in Batam City. Meanwhile, risk has no effect on the interest in using e-wallets for students in Batam City.